Pengenalan Edupreneurship Sebagai Strategi Membangun Karakter Kemandirian Siswa Smp 02 Kedungwuni - Alis Kholisoh; Wildan Khairil Anam; Arsya Ma’wa Ni’matul Izzati; Suci Rahmania Suci Rahmania (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2026)
Write abstract in English. Use Book Antiqua 11 for body of the abstract with one spacing between lines, justified, consists of 150-200 words. Inform; the issue, purpose (contains objectives of the research), method (delivers data collection of the research), results of the research (refers to collected data as an effort to answer research question), impact and conclusion (summary of the finding and the result of the research). This study aims to explore in depth the application of edupreneurship in developing students' independence at SMP Negeri 2 Kedungwuni, Pekalongan Regency. The concept of edupreneurship integrates entrepreneurial principles into education to foster creative, innovative, and independent attitudes from an early age. Using a qualitative descriptive method through observation and interviews, the results of the study show that students responded very positively to practice-based learning materials and methods, such as simulations and games, which proved effective in increasing enthusiasm, active participation, self-confidence, and discipline. The school supports this initiative, despite facing challenges such as student character variations and the need for strengthening curriculum planning and teacher training. Overall, the implementation of edupreneurship has made a significant contribution in bridging theory and practice, and has successfully shaped an entrepreneurial mindset that is essential for students' future life readiness and independence development